New Jersey Home Health Care Aides Survey Results. Issue 3 (August 2019) - Ridenour, Marilyn Lou; Hendricks, Scott; Hartley, Daniel; Blando, James D.
The objective of the study was to report on what violence-based training home health care aides received, their participation in health promotion classes, and home health care aides' experience with workplace violence. In 2013, a mail survey was completed by 513 home health care aides in the state of New Jersey. Ninety-four percent of the respondents were female. Respondents whose agency was part of a hospital were more likely to receive violence-based safety training than respondents whose agency was not part of a hospital ( p = .0313). When the perpetrator of violence was a patient or family member, the respondents experienced verbal abuse the most (26%), then physical assault (16%) and exposure to bodily fluids (13%). Home health care aides whose agency was part of a hospital were more likely to receive violence-based safety training. Training is an important component of a workplace violence prevention program.